Fractionation of anaerobic digestates by dynamic nanofiltration and reverse osmosis: An industrial pilot case evaluation for nutrient recovery. Issue 5 (October 2018) - Adam, Gilles; Mottet, Alexis; Lemaigre, Sébastien; Tsachidou, Bella; Trouvé, Emmanuël; Delfosse, Philippe
Graphical abstract: Highlights: Water recovery rate of 10–12% was obtained with two industrial pilots. Nanofiltration retained >95% of organic matter of the digestate liquid fraction. Nanofiltration retained >90% of the phosphorus of the digestate liquid fraction. Organic NPK and mineral NK fertilizers were obtained over filtration process. Electrical energy consumption was of 11.6 kWhel  t −1 digestate . Abstract: Two industrial-scale membrane filtration pilots were evaluated on their ability to separate organic matter, nutrients and water from digestates. Both pilots were equipped with a screw press for solid-liquid separation, followed sequentially by a dynamic nanofiltration treating the liquid phase of digestates and two reverse osmosis filtrations. The prototypes were efficient in nutrient recovery and separation. Indeed, the nanofiltration concentrate represented 45–55% of the output fraction and concentrated >90% of the organic matter, >95% of phosphorus and >90% of the organic nitrogen of the digestate liquid fraction. Two groups of fertilizers were obtained: (i) organic NPK fertilizers including solid fractions of the digestate and retentates of nanofiltration (5–8% wet weight (ww) of organic matter, 0.16–0.35%ww P2 O5 and a total NPK content of 1.1–1.45%ww), and (ii) mineral NK fertilizers composed of retentates of reverse osmosis filtration (ammonia nitrogen: 0.2–0.43%ww N; potassium: 0.22−0.73%ww K2 O). Water recovery rate was 10–12% of the digestate liquid phase input. Chemical oxygen demand and total suspended solids in permeate water were 27–37 mgO2 L −1 and 2–2.5 mg L −1, respectively, whereas the ammonia nitrogen and potassium content was above 600 mg L −1 . Energy consumption was 11.6 kWhel t −1 digestate . Dynamic nanofiltration combined with low-pressure reverse osmosis constitutes a valuable technique for nutrient recovery and fractionation in anaerobic digestates with low energy consumption. However, this technique is still in need of further optimization, especially for both ammonia nitrogen and potassium retention, and water recovery.